1995
DOI: 10.1111/j.1600-0447.1995.tb09780.x
|View full text |Cite
|
Sign up to set email alerts
|

The outcome of adolescent suicide attempts

Abstract: A sample of 265 adolescents hospitalized between 1971 and 1980 in a psychiatric unit following a suicide attempt was studied to evaluate outcome. After an average of 11.5 years, 48% of the original sample, or 127 subjects, could be traced. Thirty-nine per cent of these subjects showed signs of improvement, 22% appeared to be unchanged and 33% were worse. Substantial dropout rates were found in postdischarge care, only 32% of the patients having been followed up for a sufficient amount of time. Fifteen subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 27 publications
1
29
0
1
Order By: Relevance
“…While girls repeat suicide attempts more often, they take their own lives less often than boys, which should entail a higher rate of care for boys. But the dierence in recommended aftercare registered in this study may perhaps be due to a more negative attitude towards care among boys than among girls of the same age (6,8), as well as due to more negative attitudes of clinicians to boys with suicide attempts who have personality disorders (2, 31±33).…”
Section: Dierences Of Recommended Aftercare For Girls and Boys Betweementioning
confidence: 82%
“…While girls repeat suicide attempts more often, they take their own lives less often than boys, which should entail a higher rate of care for boys. But the dierence in recommended aftercare registered in this study may perhaps be due to a more negative attitude towards care among boys than among girls of the same age (6,8), as well as due to more negative attitudes of clinicians to boys with suicide attempts who have personality disorders (2, 31±33).…”
Section: Dierences Of Recommended Aftercare For Girls and Boys Betweementioning
confidence: 82%
“…For example, in a large cohort of adolescents (Fergusson & Lynskey, 1995), youths who reported a past suicide attempt (at or prior to age 14) were 17 times more likely to be diagnosed (at age 16) with a mood disorder, 5 times more likely to be diagnosed with an anxiety disorder, and 13 times more likely to be diagnosed with conduct disorder. In addition, a follow-up study of adolescent suicide attempters found that 55% had the same or worse psychosocial functioning 11 years postattempt (Granboulan et al, 1995).…”
Section: Suicidality and Psychological Distress At Follow-upmentioning
confidence: 99%
“…For example, in a large cohort of adolescents (Fergusson & Lynskey, 1995), youths who reported a past suicide attempt (at or prior to age 14) were 17 times more likely to be diagnosed (at age 16) with a mood disorder, 5 times more likely to be diagnosed with an anxiety disorder, and 13 times more likely to be diagnosed with conduct disorder. In addition, a follow-up study of adolescent suicide attempters found that 55% had the same or worse psychosocial functioning 11 years postattempt (Granboulan et al, 1995).If we can generalize from heterosexual youths to GLB youths, we would expect that GLB youths who attempt suicide would have high levels of psychological distress for some time following their suicidality. Among GLB youths, significant relations have been found between suicidality and psychological distress (e.g., Hershberger & D'Augelli, 1995;Russell & Joyner, 2001;Safren & Heimberg, 1999).…”
mentioning
confidence: 99%
“…For example, in a 6-year follow-up Nardini-Maillard and Ladame (1980) found that 3.8% of their original sample of 130 adolescent suicide attempters had died by suicide. Similarly, in another French study, 3.9% of 127 patients traced had committed suicide by the time of follow-up (mean follow-up time 11.5 years; Granboulan et al, 1995). These rates may underestimate the true incidence of completed suicide, since some of the adolescents who were untraceable in these studies may have been deceased.…”
Section: Completed Suicidementioning
confidence: 99%
“…For example, an active method of attempt, such as hanging or use of a firearm, is more likely to result in a future completed suicide than a passive method of attempt, such as ingestion (Otto, 1972;Granboulan et al, 1995). In Otto's (1972) study, 70% of adolescents who later went on to commit suicide did so by the same method that had characterized their initial attempt.…”
Section: Completed Suicidementioning
confidence: 99%